RANCANG BANGUN SISTEM MONITORING DAN KONTROL INFUS DENGAN PENERAPAN INTERNET of THINGS (IoT) BERBASIS ANDROID - Halifatullah, Ismail; Sulaksono, Danang Haryo; Tukadi, Tukadi (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
Infusion is considered a vital device for health which in certain condition, it serves for substituting liquid loss and balancing the body’s electrolyte. Therefore, a system for monitoring and controlling the condition of infusion from far areas in the real time is required. Building such system needs some sensor components among others photodiode for monitoring the droplets of infusion, load cell for monitoring the weight of infusion bottle, RGB sensor TCS34725 for monitoring the clogging of blood, and Wi-Fi module esp8266 for applying the concept of Internet of Things in the system. The results of testing this control system got the accuracy by 80% and the manual accuracy was 70%. Thus, the accuracy difference between manual and system was 87.5%. Meanwhile, the success level of data delivery in this monitoring system was 90%. In conclusion, the value showing the difference of accuracy levels indicated that the control system could stabilize infusion droplets. Moreover, the success of data delivery demonstrated that the sensor of monitoring system implementing Internet of Things could run well.